(untitled) (Journal of Surgery and Medical Case Reports, 2026)
Background: Right lower abdominal pain is a frequent emergency presentation with varied differential diagnoses. Valentino syndrome describes a perforated gastric or duodenal ulcer presenting as acute appendicitis due to tracking of gastrointestinal contents to the right iliac fossa. Case Summary: A 28-year-old male presented with obstipation, non-bilious vomiting and acute lower abdominal pain. Examination showed tachycardia, tachypnoea and diffuse abdominal tenderness with guarding. Plain radiograph revealed pneumoperitoneum. Exploratory laparotomy revealed an inflamed appendix with purulent collection in the right iliac fossa, for which appendicectomy was performed. Further exploration identified a perforation at the junction of the first and second parts of the duodenum, which was repaired with a modified Graham patch. The postoperative course was uneventful. Conclusion: Valentino syndrome should be considered in patients presenting with right lower abdominal pain, especially in resource-limited settings where advanced imaging is not readily available. Thorough intra-operative assessment is essential for correct diagnosis and management.